Penerimaan Diri Tunanetra Adventif - Viera Bardiana; Rinaldi Rinaldi (Jurnal Halaqah, 2020)
This study aims to determine self-acceptance in adventitious blindness. This is a qualitative phenomenological study and data were analyzed using the IPA (Interpretative Phenomenological Analysis). Three adventitious blindness, aged 20-40 years had participated in this study. This study uses interviews and observation techniques. The results of this study indicate that individual self- acceptance starts from the phase of shock, adjustment, acceptance until there is new hope. Shock phases occur at the beginning of blindness. While the adjustment please is in the form of changes in the subject's attitudes and the accepting phase until the emergence of new hopes for the subject. The dynamics that occur in each individual are different to be able to accept the condition of the self. Gathering with other blind people and feeling more fortunate to be one of the things that affect the subject's self-acceptance in this study.